Photoswitchable 2‐Phenyldiazenyl‐Purines and their Influence on DNA Hybridization. Issue 11 (7th August 2020) - Grebenovsky, Nikolai; Hermanns, Volker; Heckel, Alexander
Abstract: Recently, photochromic derivatives of nucleobases have drawn attention for regulating oligonucleotide hybridization with light for photopharmacological applications. The nucleobase moiety provides attractive interaction for hybridization, whereas the photochromic moiety can alter the interaction upon irradiation due to conformational changes. Herein we report the synthesis of 2‐phenyldiazenyl‐substituted 2'‐deoxyadenosine (dAAzo ) and 2'‐deoxyguanosine (dGAzo ) and investigate their influence in a DNA context by UV/Vis absorption, fluorescence and CD spectroscopies. For comparison, the literature‐known azobenzene C ‐nucleoside DNAzo was used as a reference system. It could be shown that photochromic purines improve overall hybridization affinity compared to azobenzene C ‐nucleosides. In particular, 2'‐deoxyadenosine analogue dAAzo increases melting temperatures by 7.5 °C in the favored trans state with 86 % of the switching efficiency of the reference system. Abstract : Photochromic nucleobases provide an interesting tool for controlling oligonucleotide hybridization with light. Here we report the synthesis of 2‐phenyldiazenyl derivatives of 2'‐deoxyadenosine and –guanosine and investigate their influence on DNA hybridization by UV/Vis absorption, fluorescence and CD spectroscopies.